(untitled) (European Journal of Behavioral Sciences, 2020)
Subjective well-being (SWB) has been widely associated with quality of life and health outcomes. In the organizational and work context, SWB has been also related to better outcomes, like higher levels of job satisfaction, productivity and enhanced career development. Yet in the present context of economic pressure and highly dynamic work markets employees are asked to be better at taking risks to come with fast and creative solutions and companies are facing the challenge of recruiting best equipped individuals and assuring the conditions for them to be at their best. Personal and organizational characteristics, like personality and psychological safety seen to play an important role in these matters. However, it is still to know how are these variables associated with the employees’ well-being. The aim of this study is to explore the impact of open to experience, resilience and psychological security on SWB. A sample of 193 Portuguese adults working in 20 companies of the industry and IT sectors answered a standardize questionnaire. In order to explore what and to what extent personal (open to experience and resilience) and organizational (psychological safety) variables impact SWB the multiple regression models were computed. Results showed that the most associated variable in the three models is resilience and that the three predictors have higher impact on explaining Life Satisfaction (29.5%) and Positive Affect (26.5%).